2021
DOI: 10.37058/bioed.v6i1.2697
|View full text |Cite
|
Sign up to set email alerts
|

TPACK: Analysis of Biology Learning Outcomes at Senior High School Level`s in the Bandar Lampung City During Online Learning

Abstract: The purpose of this study was to analyze students' biology learning outcomes towards the achievement of basic competencies in biology materials at senior high school and to evaluate the implementation of online biology learning for teachers and students in order to achieve the expected competencies. The research design used an ex post facto design, with the population being all state senior high school students in the city of Bandar Lampung in a different distribution of sub-district locations represented base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Proses pembelajaran pada pembelajaran sains terjadi dengan menyajikan kajian secara teoritis maupun praktis (Sujana, et al, 2014). Permasalahan yang ditemui oleh sejumlah pendidik sains adalah kesulitan dalam menerapkan proses pembelajaran yang praktis secara daring, karena sains sangata dekat dengan fakta yang teramati yang menyertakan kegiatan penggunaan laboratorium Maulina, 2021). Dalam seting praktikum di laboratorium yang berstruktur dan dikendalikan secara ketat, akan sukar menciptakan kegiatan yang menimbulkan rasa otonomi pada peserta didik (Likita, et al, 2020).…”
unclassified
“…Proses pembelajaran pada pembelajaran sains terjadi dengan menyajikan kajian secara teoritis maupun praktis (Sujana, et al, 2014). Permasalahan yang ditemui oleh sejumlah pendidik sains adalah kesulitan dalam menerapkan proses pembelajaran yang praktis secara daring, karena sains sangata dekat dengan fakta yang teramati yang menyertakan kegiatan penggunaan laboratorium Maulina, 2021). Dalam seting praktikum di laboratorium yang berstruktur dan dikendalikan secara ketat, akan sukar menciptakan kegiatan yang menimbulkan rasa otonomi pada peserta didik (Likita, et al, 2020).…”
unclassified
“…Several researchers have attempted to develop TPACK for preservice teachers, especially in biology (TPACK in biology). Most of the TPACKs that describe the competencies of prospective biology teachers still refer to certain courses or content (Kotzebue, 2022;Maulina et al, 2021;Nuruzzakiah et al, 2022). TPACK in biology is considered essential and relevant for preparing preservice biology teachers to face a new century of teaching biology.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of online learning specifically when it is implemented in science learning will be the main topic of study and how are the ideal conditions for learning science online (Maulina et al, 2021). The nature of science learning, proof, and truth in a field of scientific study is proven based on the observed facts obtained through the results of real empirical data that are contextual in nature (Maulina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional involvement in the online learning process provides a significant response and progress to learning outcomes. Many previous studies have revealed the advantages and disadvantages of implementing online learning (Maulina et al, 2021). The previous study showed that there had been a significant effect on PjBL with students' intrinsic factors.…”
Section: Introductionmentioning
confidence: 99%